Intergenerational Trauma and Cultural Resilience: Exploring the Impact of Family Norms on Mental Health Disclosure - Disha Tyagi; Kajal Tomar; Deepika Chamoli Shahi (International Journal of Behavioral Sciences, 2025)
This comprehensive review examines how intergenerational trauma and cultural resilience influence individuals' choices to disclose or conceal their mental health challenges in family contexts. This paper utilizes 50 peer-reviewed studies out of 80 in total from various cultural contexts, this paper explores how family norms, especially in collectivist cultures, impact the disclosure of mental health issues. This review paper uses a thematic analysis strategy, systematically integrating qualitative, quantitative, and mixed-method studies to identify recurring themes associated with trauma transmission, emotional expression, and resilience strategies. Results show that in numerous families, particularly those influenced by historical or collective trauma, silence frequently serves as a protective strategy, maintained by entrenched beliefs regarding emotional control and anxiety over stigma. On the other hand, cultural resilience demonstrated through community bonds, customs, and common identity acts as a counterbalance, promoting emotional vulnerability and group recovery. The analysis highlights the interplay between trauma and resilience in families, affecting whether mental health discussions are stifled or promoted. In the end, it supports culturally aware mental health approaches that acknowledge historical suffering while leveraging cultural strengths to facilitate safe and open conversations. The review underscores how intergenerational narratives, parental coping mechanisms, and social expectations shape individuals’ willingness to engage in emotional disclosure. It also emphasizes that interventions focusing on culturally sensitive communication and family-based healing frameworks are more effective in reducing stigma and enhancing psychological well-being. Overall, this paper contributes to the growing recognition of culture-specific pathways in mental health discourse, stressing the importance of understanding trauma and resilience not as opposing forces but as interconnected processes shaping collective healing.
Keywords: Cultural Resilience; Family Norms; Intergenerational trauma; Mental Health Disclosure; Thematic analysis